Exploratory research of intelligent gecko-inspired robot based on integrated design and experiment - Haifei Qiu; Jiayou Zhang; Jing Zhao; Chaohui Wang; Chengchuang Li (Heliyon, 2024)
A quadruped robot with intelligent properties is developed using a bionics approach to explore the potential value of gecko-like machinery. The robot structure incorporates mechanical links, steering engines, and wheel groups, which can expand the movement function of its leg joint. A pneumatic control circuit that can generate negative pressure is built by a vacuum pump, electromagnetic valve, sucker, hose, and others, to enable mobile climbing and adsorption of the gecko-inspired robot. By integrating gait planning, program compilation, Arduino board development, theoretical calculation, and digital modeling, the robot incorporates several practical functions such as “adsorption climbing, ultrasonic obstacle avoidance, remote control, Bluetooth communication, WiFi wireless image transmission, and multi-terrain maneuvering,” which give a basis to realize the multi-dimensional integrated design of “machine, electricity, gas and intelligence” of biomimetic gecko. The experimental prototype of the gecko-inspired robot is designed and manufactured with 3D printing, combined with virtual prototype development, mechanism trajectory verification, finite element analysis, and CFD hydrodynamic simulation. Test results indicate that the biomimetic body has ideal characteristics of intelligent control and maneuvering response in the natural environment, which specifically manifested as that the robot can carry out stable adsorption and climb on the vertical wall, respond quickly to avoid obstacles intelligently, and detect and monitor the external environment in real-time with the help of a mobile phone control terminal. This work is promising for solving high-risk social production and engineering operation challenges.